2004
DOI: 10.1002/chem.200305096
|View full text |Cite
|
Sign up to set email alerts
|

From D‐Glucose to Biologically Potent L‐Hexose Derivatives: Synthesis of α‐L‐Iduronidase Fluorogenic Detector and the Disaccharide Moieties of Bleomycin A2 and Heparan Sulfate

Abstract: A novel and convenient route for the synthesis of biologically potent and rare L-hexose derivatives from D-glucose is described. Conversion of diacetone-alpha-D-glucose (14) into 1,2:3,5-di-O-isopropylidene-beta-L-idofuranose (19) was efficiently carried out in two steps. Orthogonal isopropylidene rearrangement of compound 19 led to 1,2:5,6-di-O-isopropylidene-beta-L-idofuranose (27), which underwent regioselective epimerization at the C3 position to give the L-talo- and 3-functionalized L-idofuranosyl derivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 87 publications
0
25
0
Order By: Relevance
“…The 1 H NMR spectrum of the orthoester 7 had two sets of signals due to the presence of two diastereoisomers in a ratio of 10:3. Hung has also reported the formation of orthoester as the major product on subjecting a similar α‐ l ‐glycosyl chloride to glycosylation with methanol using AgOTf as promoter . Similarly, Whitfield[9b] reported that glycosylation of methanol with a related IdoA‐configured glycosyl bromide also gave orthoester as the major product and interestingly, the β‐ l ‐glycoside as a minor product with no trace of α‐ l ‐glycoside.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The 1 H NMR spectrum of the orthoester 7 had two sets of signals due to the presence of two diastereoisomers in a ratio of 10:3. Hung has also reported the formation of orthoester as the major product on subjecting a similar α‐ l ‐glycosyl chloride to glycosylation with methanol using AgOTf as promoter . Similarly, Whitfield[9b] reported that glycosylation of methanol with a related IdoA‐configured glycosyl bromide also gave orthoester as the major product and interestingly, the β‐ l ‐glycoside as a minor product with no trace of α‐ l ‐glycoside.…”
Section: Resultsmentioning
confidence: 98%
“…Despite earlier reports, of the successful synthesis of 3 using titanium tetrabromide, in our hands the bromide 3 was found to be highly reactive and unstable. Hung has also reported that a similar l ‐idosyl bromide is unstable and is readily hydrolyzed to the hemiacetal …”
Section: Resultsmentioning
confidence: 99%
“…Compounds 1a-1d were chosen as model structures, to investigate the potential of benzylamine in promoting the substitution of the tosylate group (Figure 1). Isopropylidene acetals 1a [25], 1b [26] and 1c [10,27] were synthesized according to literature procedures. Whereas 1d was achieved from the elaboration of known dimethyl ether 4 [28] which was treated initially with aqueous (aq.)…”
Section: Resultsmentioning
confidence: 99%
“…Isopropylidene acetals 1a [25], 1b [26] and 1c [10,27] were synthesized according to literature procedures. Whereas 1d was achieved from the elaboration of known dimethyl ether 4 [28] which was treated initially with aqueous (aq.) 60% acetic acid (AcOH) to obtain 5 in 72% yield [29].…”
Section: Resultsmentioning
confidence: 99%
“…Commercially available from the 1960s, 4-methylumbelliferyl glycosides, such as 4-methylumbelliferyl-α/β-D-glucopyranoside, 4-methylumbelliferyl-β-D-cellobioside, 4-methylumbelliferyl-β-D-galactopyranoside, and 4-methylumbelliferyl-N-acetyl-β-Dglucosaminide, have been used for the identification, characterization and kinetic study of glycosidases [58][59][60][61]. Cleavages of the glyco linkage in these glycosides, such as 4-methylumbelliferyl-β-D-glucopyranoside 22, by glycosidases lead to the formation of fluorescent 4-methylumbelliferone 23 (Scheme 4).…”
Section: Fluorogenic Glycosidase Substratesmentioning
confidence: 99%